Advancements in the conservation of the conformational epitope of membrane protein immunogens - Mahboob, Aisha; Fatma, Nishat; Faraz, Ahmed; Pervez, Muntaha; Khan, Mohammad Afeef; Husain, Afzal (Frontiers in Immunology, 2025)
Generating antibodies targeting native membrane proteins presents various challenges because these proteins are often embedded in the lipid bilayer, possess various extracellular and intracellular domains, and undergo post-translational modifications. These properties of MPs make it challenging to preserve their stable native conformations for immunization or antibody generation outside of the membranes. In addition, MPs are often hydrophobic due to their membrane-spanning regions, making them difficult to solubilize and purify in their native form. Therefore, employing purified MPs for immunogen preparation may result in denaturation or the loss of native structure, rendering them inadequate for producing antibodies recognizing native conformations. Despite these obstacles, various new approaches have emerged to address these problems. We outline recent advancements in designing and preparing immunogens to produce antibodies targeting MPs. Strategies outlined here are relevant for producing antibodies for research, diagnostics, and therapies and designing immunogens for vaccination purposes.